2005
DOI: 10.1038/sj.ejcn.1602121
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive food stimulants of sympathetic activity: effect on 24-h energy expenditure and fat oxidation

Abstract: Objective: Bioactive food ingredients influence energy balance by exerting weak thermogenic effects. We studied whether the thermogenic effect of a combination of capsaicin, green tea extract (catechins and caffeine), tyrosine, and calcium was maintained after 7-day treatment and whether local effects in the gastric mucosa were involved in the efficacy. Design: The present study was designed as a 3-way crossover, randomised, placebo-controlled, double-blinded intervention. Setting: Department of Human Nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
29
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 43 publications
6
29
1
1
Order By: Relevance
“…35) Belza et al have reported that the intake of a combination of capsaicin, caffeine, catechins, L-tyrosine, and calcium for seven days increased the energy expenditure by about 40 kcal/ day. 36) In the present study, the body weight was decreased by 1.7 kg by the intake of CH-19 Sweet, the calculated increase in energy expenditure by the degree of weight loss being 350-500 kcal/day. The effect of CH-19 Sweet was greater than that in these previous reports.…”
Section: Discussionmentioning
confidence: 86%
“…35) Belza et al have reported that the intake of a combination of capsaicin, caffeine, catechins, L-tyrosine, and calcium for seven days increased the energy expenditure by about 40 kcal/ day. 36) In the present study, the body weight was decreased by 1.7 kg by the intake of CH-19 Sweet, the calculated increase in energy expenditure by the degree of weight loss being 350-500 kcal/day. The effect of CH-19 Sweet was greater than that in these previous reports.…”
Section: Discussionmentioning
confidence: 86%
“…Human data suggest that adding chilli to a meal lowers total energy and macronutrient intake (Yoshioka et al, 1999;Yoshioka et al, 2001;Yoshioka et al, 2004;Belza and Jessen, 2005). Chilli also increases postprandial energy expenditure (EE) (Henry and Emery 1986;Yoshioka et al, 1995;Yoshioka et al, 1998), fat oxidation in women (Yoshioka et al, 1998) and carbohydrate oxidation in men (Yoshioka et al, 1995;Lim et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are only two small to mediumlong-term studies that have investigated the effects of regular intake of the active ingredient of chilli (capsaicin) on metabolism in adult humans (Lejeune et al, 2003;Belza and Jessen, 2005). One study (Belza and Jessen, 2005) reported a 'tendency' towards increased energy expenditure after 1 week of regular capsaicin intake (0.6 mg/day) and the other (Lejeune et al, 2003), reported the beneficial effect of capsaicin (135 mg/day) in sustaining fat oxidation after a period of weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…9) Belza et al have reported that the ingestion of CAPcontaining tablets which dissolve in the stomach increased the energy expenditure, whereas the same tablets dissolving in the small intestine had no such effect. 25) These reports suggest that the local action of CAP in gastric mucosa is a prerequisite for exerting the thermogenetic effect. Orally administered 1-MGs might therefore increase the expression of UCP1 protein and prevent WAT accumulation by activation of the TRPV1-expressing sensory nerve distributed in the upper gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%